The prognostic value of cytokine levels in patients with cancer - Kamińska, Janina; Kowalska, Maria; Kotowicz, Beata; Fuksiewicz, Małgorzata (Contemporary Oncology/Współczesna Onkologia, 2006)
We have demonstrated that the serum levels of many cytokines and soluble cytokine receptors are increased in a great proportion of patients with ovarian cancer, colorectal cancer, non-small cell lung carcinoma and soft tissue and bone sarcomas. In addition, the elevated concentrations of some cytokine/cytokine receptor are present in patients already in the early stages of the diseases, and relate to clinicopathologic characteristics, such as clinical stage, tumour grade and tumour size. Interestingly, in many cancer types, multiple cytokines and soluble cytokine receptors characterised by different activities are increased in parallel. Of the numerous cytokines and cytokine receptors that have been studied, sTNF RI, IL-6, IL-8, M-CSF, VEGF and sTNF RII are most frequently increased. It is noteworthy that while the levels of TNF-α are mostly normal, the concentrations of its receptors, especially of the sTNF RI, are commonly increased. The levels of some cytokines/cytokine receptors proved to be independent prognostic factors, i.e. of sTNF RII and VEGF in ovarian cancer, of sTNF RI in colorectal cancer, of M-CSF in non-small cell lung carcinoma, of IL-6 and IL-8 in soft tissue sarcoma and of sTNF RI and IL-1ra in bone sarcoma. Circulating cytokine and cytokine receptor measurements along with the standard tumour marker assessments, may not only serve as prognostic tools in cancer patients, but also provide grounds for individual optimisation of treatment